Principal's Strategy in Improving Teacher Performance - Cittra Juniarni; Anwar Sa’dullah; Ahmad Luviadi; Devi Pramitha; Nikma Nikma (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: This study aims to determine the principal's strategy in improving teacher performance and the supporting and inhibiting factors of principals in improving teacher performance in educational institutions. Background Problems: indicators of problems in academic institutions such as the rare collection of lesson plans (RPP) in carrying out the teaching and learning process and teachers who lack discipline in punctuality in arriving and opening lessons and ending lessons. Novelty: Principal strategy concept in improving teacher performance in educational institutions. Research Methods: The type of field research means that the researchers used a qualitative method in which the data were in the form of words (not numbers) derived from data collection techniques, namely interviews, observation, and documentation. Finding/Results: The data analysis technique used is data reduction, data presentation, and conclusion drawing. Conclusion: The results of the research on the principal's strategy to improve teacher performance by 1) fostering teacher performance in seminars and training, 2) supervision or supervision of performance in the form of class visits every week and once a month, 3) fostering discipline of education staff by supervising the presence of teachers directly, 4 ) provide motivation 5) award. Supporting factors for principals to improve teacher performance are 1) completeness of facilities and infrastructure and 2) teacher enthusiasm to improve teaching performance. While the inhibiting factors are: 1) the lack of discipline of the teacher, 2) the mastery of the material and references, causing the teacher to be less mature in teaching preparation.